Axial compressive behavior of GFRP tube confined seawater coral aggregate concrete reinforced with epoxy-coated bars. (15th June 2021) - Ying, Jingwei; Huang, Yijie; Qin, Li; Gao, Xu; Wang, Zhankui
Abstract: An experimental study on the mechanical behavior of glass fiber reinforced plastic (GFRP) tube confined seawater coral aggregate concrete reinforced with epoxy-coated steel bars (GSCACESB) under axial compression were systematically performed. Three different parameters were considered: concrete type (seawater coral aggregate concrete and ordinary concrete), GFRP tube thickness (4 mm, 5 mm and 6 mm) and reinforcement ratio (longitudinal and circumferential reinforcement ratios). Typical influences of concrete, GFRP tube and reinforcement on the bearing capacity, deformation and load-deformation curve of GSCACESB were investigated. Test results showed that the failure pattern of GSCACESB was similar to that of GFRP tube confined ordinary concrete (GCOC). However, the bearing capacity of GSCACESB was significantly decreased compared to GCOC due to the less confinement between seawater coral aggregate concrete and outer tube. The peak deformation and bearing capacity of GSCACESB increased with the increases of tube thickness, and longitudinal and circumferential reinforcement ratios. The load-deformation curve of GSCACESB was divided into elastic-plastic and hardening stages. The more the reinforcement ratio, the less the curve curvature. An analytical expression considering the influences of SCAC was also proposed, which could predict the structural response of GSCACESB. Finally, the numerical simulation analysis was undertaken to investigate the GSCACESB mechanical behaviors.